Revision of the genus Parequula (Pisces: Gerreidae) with a new species from southwestern Australia - Iwatsuki, Yukio; Pogonoski, John J.; Last, Peter (Zootaxa, 2012)
The genus Parequula, which has long been considered monotypic, is reviewed with a new species described fromsouthwestern Australia on the basis of 21 types and 17 non-type specimens (42–81 mm in standard length); its onlycongener, P. melbournensis (Castelnau), is also redescribed. Parequula elongata n. sp. differs from P. melbournensis inhaving a more slender body, a lower soft anal-fin ray count (14–15, mode 15 vs. 16–18, mode 17), a lower pored lateral-line scale count (34–35, mode 34 vs. 37–40, mode 38), and the dorsal fin with a reddish upper margin when fresh (vs.semi-translucent to bluish with a narrow, parallel, yellowish vertical line on each fin membrane and a yellowish fin marginin P. melbournensis). Furthermore, the head profile of P. elongata n. sp. is nearly straight to slightly convex, whereas P.melbournensis is distinctly concave in outline above the eyes. Nominal species (junior synonyms) of P. melbournensis are discussed and a key to the two species is also provided.